The Role Of Parents In Instilling Independence In Early Childhood In Batang Kulur Kiri Village, Hulu Sungai Selatan Regency - Rizki Noor; Noorliyana Hasanah; Hj. Ikta Yarliani (Tajdid Al-Athfal, 2023)
A person's low level of independence will become an obstacle for him in living his life in the future. So, it is important for parents to train and instill independence in their children from an early age. The aim of this research is to determine the role of parents in forming and instilling independence in children from an early age, as well as to find out the obstacles faced by parents in forming children's independence from an early age. The subjects in this research were parents who work as traders and have children aged 4-6 years, as well as children aged 4-6 years who live in Batang Kulur Kiri Village. The approach used in this research is qualitative and is a case study type of research. Data collection techniques were carried out using observation, interviews and documentation. Data processing and analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. Based on the results of this research, the parents in Batang Kulur Village who are the subjects of this research have succeeded in instilling and forming their children into independent individuals. This independence is instilled from an early age, starting with providing a good example, providing training and guidance, and continuing with providing habituation. The obstacle faced by parents in instilling independence in children is the lack of cooperation between the two parents or between parents and other parties not to spoil the child. Apart from that, there is a lazy attitude in children, as well as advances in technology and mass media are also obstacles in instilling independence in children